ANALISA PENGARUH CLEANING TUBING KONDENSOR TERHADAP KINERJA CHILLER I DI BANDAR UDARA SULTAN MAHMUD BADARUDDIN II PALEMBANG - M. Ismail, KGS.; Sukma Wardana, Siddiq; Cheisa Pratiwi , Salsa (Program Studi Teknik Mekanikal Bandar Udara, 2024)
Chiller is one of the equipment in Air Conditioning System that functions as a heat exchanger. At the airport, Chiller functions as a heat exchanger that will later be distributed in the airport terminal area. One of the main components of the chiller is the condenser. The condenser is a heat exchanger in a refrigeration cycle. Over time, the performance of a heat exchanger will usually decrease due to deposits/fouling on the heat transfer surface. One way that can be done to improve the performance of a Chiller is by cleaning the part that performs heat exchange or cleaning the condenser tubing. Therefore, it is very important to need an Analysis of the Effect of Cleaning Condenser Tubing on Chiller Performance at Sultan Mahmud Badaruddin II Airport, Palembang. This analysis was carried out on a Carrier brand Chiller with a model of 19XR-4647836CLH52 with a capacity of 350 TR. It is estimated that this journal will find a difference in the effectiveness of Chiller performance before and after cleaning the condenser tubing.